EXPERIMENTAL STUDY ON THE COMBUSTION AND EXHAUST EMISSIONS OF OTTO ENGINE FUEL WITH NAPHTHALENE-GASOLINE BLENDS (Diyala Journal of Engineering Sciences, 2017)
The growing demand of energy in transportations especially in small cars field leads to increase the contribution of this vital sector of modern life in the greenhouse effect and environment problems. Any enhancement in the thermal efficiency of the car’s engines will reduce the amount of bad effects gases that released from gasoline engines exhausts. Rising Octane number and or enhance the combustion process result in increasing of engine output power. Naphthalene as mothballs, which is a commonly household used in exclusion of harmful insects, is probable additive to achieve that. The usage of Naphthalene needs to study its impacts on the performance of Otto cycle’s engines and their exhaust gases. Blends of Naphthalene as additive and gasoline as base material have been prepared and examined. The study based on experimental tests and laboratory assays including; Octane number calculations, Fourier Transform Infrared Spectroscopy analysis (FTIR), Gas Chromatography Mass Spectrometry analysis (GCMS) and thermal performance tests and emissions analysis. Naphthalene had been approved as a good additive to rise the octane number and output power with some caveats. It should carefully control Naphthalene concentration to avoid the side effects of overdose and should not directly dissolved in the car fuel tank to prevent the formation of the deposits.